Medication Adherence of Older Adults with Diabetes Mellitus Type II - Hutapea, Dwight Mahaputera Marulitua (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
Older people with diabetes mellitus type II are more likely to develop hyperosmolar non-ketotic coma and have worst outcomes, like higher mortality than middle-aged people with diabetes mellitus type II. To prevent and control diabetes mellitus type II and complications for older adults by decreasing HbA1c and increase medication adherence and self-care behavior. Older adults who are unfunctional of their cognitive impact because of the process of ageing impaired cognitive behavior. To review the evidences of medication adherence in older adults with type II Diabetes Mellitus.The selection process of the articles have been done by using this data based provided by Prince of Songkla University. The data base was selected for this study are Cinanhl, Proquest, Science Direct, and PubMed. By using this data base the search terms according to PICO a total of eighty (80) have been found. From the overall thirtieth (30) relevant articles closely related to this study. Five studies were reviewed with two types of interventions for medicaiton adherence in older adult patients: Patient education (teaching), and nurse telephone call intervention. The result from this five studies the intervention successfully improved medication adherence in older adults patients. Diabetes mellitus is one of the most world wild prevalent of chronic disease, where it increasing globally to such a high levels. The management of lower blood glucose level is depend on many factors, including the management of diabetes mellitus in patient’s health education in knowledge, and practice on medication adherence. Patient’s ability to do self-care in their daily lives, and therefore patients education in knowledge, attitude, and practice on medication adherence is considered an essential element of diabetes management. Patient’s education and knowledge is an important component in management of diabetes in medication adherence.